Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Les femmes de droite - Dworkin, Andrea (Les éditions du remue-ménage, 2012)
Militante féministe, Andrea Dworkin a voulu comprendre pourquoi des femmes rejettent le féminisme et n’hésitent pas à se montrer racistes et homophobes. Comment expliquer cet apparent paradoxe? Dans un contexte où les femmes sont subordonnées aux hommes, les femmes de droite concluent ce qui leur paraît le marché le plus avantageux: en échange de leur conformité aux rôles traditionnels, la droite leur promet la sécurité, le respect, l’amour. Elles font donc le pari qu’il est préférable de prendre le parti du patriarcat plutôt que de combattre ce système dont la violence est trop souvent meurtrière. Mais la droite et l’antiféminisme se fondent sur le mépris des femmes et encouragent l’exploitation de leur sexualité: «ce que font les femmes de droite pour survivre au système de classes de sexe ne signifie pas qu’elles y survivront: si elles sont tuées, ce sera probablement aux mains de leur mari.» Une réflexion brutale et sans concession, qui appelle à la révolte féministe.
Keywords: amériques; antiféminisme; approches et analyses; corps; cours; cycles supérieurs; fem1000; fem7000; lit2815; lit3220; lit3495; militance; pornographie; premier cycle; régions géographiques; sexualité; thématiques; violences; violences sexistes et sexuelles; états-unis